A comparative molecular survey of malaria prevalence among Eastern chimpanzee populations in Issa Valley (Tanzania) and Kalinzu (Uganda). (December 2016) - Mapua, Mwanahamisi; Petrželková, Klára; Burgunder, Jade; Dadáková, Eva; Brožová, Kristýna; Hrazdilová, Kristýna; Stewart, Fiona; Piel, Alex; Vallo, Peter; Fuehrer, Hans-Peter; Hashimoto, Chie; Modrý, David; et al.
Abstract Background Habitat types can affect vector and pathogen distribution and transmission dynamics. The prevalence and genetic diversity ofPlasmodium spp. in two eastern chimpanzee populations—Kalinzu Forest Reserve, Uganda and Issa Valley, Tanzania—inhabiting different habitat types was investigated. As a follow up study the effect of host sex and age on infections patterns in Kalinzu Forest Reserve chimpanzees was determined. Methods Molecular methods were employed to detectPlasmodium DNA from faecal samples collected from savanna-woodland (Issa Valley) and forest (Kalinzu Forest Reserve) chimpanzee populations. Results Based on aCytochrome -b PCR assay, 32 out of 160 Kalinzu chimpanzee faecal samples were positive forPlasmodium DNA, whilst no positive sample was detected in 171 Issa Valley chimpanzee faecal samples. Sequence analysis revealed that previously knownLaverania species (Plasmodium reichenowi, Plasmodium billbrayi andPlasmodium billcollinsi ) are circulating in the Kalinzu chimpanzees. A significantly higher proportion of young individuals were tested positive for infections, and switching ofPlasmodium spp. was reported in one individual. Amongst the positive individuals sampled more than once, the success of amplification ofPlasmodium DNA from faeces varied over sampling time. Conclusion The study showed marked differences in the prevalence of malaria parasites among free ranging chimpanzee populations living in different habitats. In addition, a clear pattern ofPlasmodium infections with respect to host age was found. The results presented in this study contribute to understanding the ecological aspects underlying the malaria infections in the wild. Nevertheless, integrative long-term studies on vector abundance, Plasmodium diversity during different seasons between sites would provide more insight on the occurrence, distribution and ecology of these pathogens.